1981
DOI: 10.1136/bjsm.15.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of sprinting: decathletes versus champions.

Abstract: The purpose of this study was to compare some biomechanical variables of decathletes and world class sprinters while running the 100 metre race. Sixteen Swiss national decathletes and three world class American sprinters were filmed by a 16 mm Locam (100 fps) camera at the 70 m mark of the race. The co-ordinates for a 26-point stick figure were digitised and then submitted to analysis by a computer programme which produced quantitative data for 12 biomechanical variables. The data indicated that world-class sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
11

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 1 publication
2
46
0
11
Order By: Relevance
“…Several authors have emphasised the importance of body configuration at the point of touchdown, specifically in terms of small touchdown distance 9,10,12,17,19,20 and small knee separation 11,13 during MVS, in addition to forward lean of the body during accelerated sprinting. 10,18 Mann & Murphy 20 expressed the two first variables in absolute horizontal distance, but we chose an angular expression to avoid the possible influence of varying dimensions among athletes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have emphasised the importance of body configuration at the point of touchdown, specifically in terms of small touchdown distance 9,10,12,17,19,20 and small knee separation 11,13 during MVS, in addition to forward lean of the body during accelerated sprinting. 10,18 Mann & Murphy 20 expressed the two first variables in absolute horizontal distance, but we chose an angular expression to avoid the possible influence of varying dimensions among athletes.…”
Section: Discussionmentioning
confidence: 99%
“…8,[10][11][12][13][17][18][19] In contrast, authors of the International Association of Athletics Federations (IAAF) Coaches Education and Certification System's sprint curriculum argue that the elite world of sprinting for more than 20 years has optimized front-side mechanics and minimized back-side mechanics. 20 According to Mann & Murphy,20 groups of variables related to these concepts can be identified during any portion of the sprint race by simply drawing a straight line through the upper body (trunk).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger ground forces can be generated at lower running speeds because the leg muscles have enough time to develop the forces needed to lift and accelerate the body during stance (Weyand et al, 2000). At speeds near 7ms -1 , however, ground contact times become very small (Kunz and Kaufmann, 1981;Mann and Herman, 1985;Mann, 1981), limiting the ability of the leg muscles to generate the ground forces needed to increase running speed still further (Weyand et al, 2000). Of particular interest in this respect is the behaviour of the ankle plantarflexors, which undergo significant periods of stretch-shortening during stance (Hennessy and Kilty, 2001;Ishikawa and Komi, 2007;Komi, 1984;Komi, 2000;Kubo et al, 2000;.…”
Section: Introductionmentioning
confidence: 99%
“…Facciono (1993) suggested that training at a supramaximal running velocity may improve chronic speed [4]. Kunz and Kaufmann (1981) study results indicated that downhill running yielded approximately 5.4% faster sprint times, compared to flat land running [5].…”
Section: Discussionmentioning
confidence: 64%